Inovasi Pembelajaran Seni Musik Pada Jenjang Pendidikan Dasar Dalam Perspektif Budaya Dan Karakter Peserta Didik - Purbawati, Sih Yunika; Naam, Muh Fakhrihun; Sugiarto, Eko (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
This research examines music learning innovations at the primary education level from the perspective of students' culture and character. Schools play an important role in developing students' character through a curriculum that includes Cultural Arts and Crafts subjects, especially music education. Music education contributes to the formation of a cultured national character, love for the country, creativity, co-operation, discipline and responsibility. This research highlights the importance of integrating Indonesian traditional music in the curriculum, with the aim of introducing and preserving the nation's cultural heritage. In addition, music learning innovations also include developing musical skills, self-expression, improving cognitive abilities, and instilling positive values through various creative methods and approaches. The research method used is content analysis to evaluate learning materials, curriculum, and related documents. The results show that innovation in music learning not only enhances art appreciation but also plays a significant role in students' character building. Technology integration and collaboration with local artists enrich the learning experience, increase student engagement, and build a strong foundation for future art and music appreciation. In conclusion, learning music at the primary education level can nurture a sense of pride in cultural identity, develop creativity, and shape students' strong and positive character.